Avaliação da ativação de neurônios nitrérgicos no sistema nervoso central de ratos submetidos à abstinência ao etanol - Bonassoli, Vívian Taciany (2010)
Ethanol chronic consumption can lead to dependence, and its discontinuation has been related to the onset of withdrawal syndrome. Although the ethanol withdrawal syndrome in humans and rats is well described, the neurobiological molecular mechanisms underlining it is still poorly understood. Many studies have suggested the involvement of nitric oxide in the development of this syndrome. The objective of this study was to observe the rats behavior during ethanol withdrawal for 24 and 48 h, as well to evaluate the neuronal activation in different regions of the CNS, using immunohistochemistry to detect Fos protein. In addition, we also evaluated nitrergic neurons activation combining Fos immunohistochemistry and NADPH-diaphorase. Male Wistar rats were divided into three groups (n = 11/grup): the first one received a balanced nutritionally diet, consisting of Sustagen M® added ethanol 8%, as the only source of food for a period of 21 days followed by abrupt ethanol discontinuation after 24h, the second group received the same treatment followed by abrupt discontinuation after 48h and the third group was the control and received the same basic diet without ethanol, but added sucrose to energetic balance. The animals were tested in the open field apparatus for ten minutes. After the behavioral tests, animals were sacrificed and their brains removed and processed to Fos protein detection and histochemistry to NADPH-diaphorase. Decreased exploratory activity was observed in animals subjected to 24h withdrawal, characterized by shorter moved distance in the open field. Increased Fos expression was detected in brain areas such as cingulated cortex (CG), piriform cortex (CP), paraventricular thalamus nucleus (PVA), paraventricular hypothalamus nucleus (PVH), lateral hypothalamus (LH), medial amigdala (AmMe), substantia nigra (SN), dorsomedial periaqueductal grey (DLPAG), dorsolateral (DLPAG) and ventrolateral (VLPAG) after 24 or 48h withdrawal. Dorsomedial hypothalamus (DMD) and anterior hypothalamus (AHA) were actived after 24h and dorsal raphe nucleus (NDR) after 48h ethanol withdrawal. Nitrergic neurons were activated in PVH, DLPAG and the dorsal part NDR after 24h ethanol withdrawal. 48h withdrawal led nitrergic neurons activation only in DLPAG. Nitrergic neurons activation in DLPAG, PVH e dorsal part NDR suggests the nitrergic neurotransmition involvement and support the participation of such areas in ethanol withdrawal syndrome.